2020
DOI: 10.1042/bsr20193823
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel biomarkers and candidate small molecule drugs in rheumatoid arthritis and osteoarthritis based on bioinformatics analysis of high-throughput data

Abstract: Background: Rheumatoid arthritis (RA) and osteoarthritis (OA) are two major types of joint diseases. The present study aimed to identify hub genes involved in the pathogenesis and further explore the potential treatment targets of RA and OA. Methods: The gene expression profile of GSE12021 was downloaded from Gene Expression Omnibus (GEO). Total 31 samples (12 RA, 10 OA and 9 NC samples) were used. The differentially expressed genes (DEGs) in RA versus NC, OA versus NC and RA versus OA groups we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…However, most of the research is concentrated on one disease at a time [ 54 , 55 ]. Recent advances in the study of RA and PD, OA and PD, RA and OA, as well as RA, OA, and PD separately, have been made by utilizing the data generated from high-throughput technologies (DNA microarrays and RNAseq), and Omics-based techniques [ 5 , 6 , 8 , 16 , 20 , 37 , 39 , 56 , 57 , 58 ]. However, their applicability is limited when it comes to identifying integrated signature molecules for RA, OA, and PD together.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most of the research is concentrated on one disease at a time [ 54 , 55 ]. Recent advances in the study of RA and PD, OA and PD, RA and OA, as well as RA, OA, and PD separately, have been made by utilizing the data generated from high-throughput technologies (DNA microarrays and RNAseq), and Omics-based techniques [ 5 , 6 , 8 , 16 , 20 , 37 , 39 , 56 , 57 , 58 ]. However, their applicability is limited when it comes to identifying integrated signature molecules for RA, OA, and PD together.…”
Section: Discussionmentioning
confidence: 99%
“…A t -test in the Limma package was performed to determine the p -value of each gene symbol. The following criteria were used to identify significant DEGs: p -value ≤ 0.05 and log2-fold change (logFC) ≥ ±1 [ 8 ]. Gene annotations were retrieved from the GEO database and prob ids were transformed into gene symbols; genes with the lowest p -values were chosen in the case of duplicate genes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PPI network (confidence score > 0.7), with KEGG annotations, was visualized using Cytoscape ( Shannon et al, 2003 ). The hub genes were identified using the Cytoscape plugin CytoHubba ( Song et al, 2020 ; Zuo et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…For the six marker genes previously identified, we found that SCRG1, CDKN1A, SLC2A3 genes were significantly expressed in all microarray and RNA-seq datasets, and only SCRG1 gene showed an increased expression trend in all datasets. SCRG1 has also been observed to be specifically expressed in human articular cartilage (29)(30)(31), so we considered that SCRG1 might be a key regulatory factor in the development of synovial inflammation. In order to understand the role of SCRG1 in OA, we performed gene expression correlation analysis to predict SCRG1 gene function by protein-protein interaction.…”
Section: Spearman Correlation Analysis Suggested the Function Of The ...mentioning
confidence: 99%